Rural Economic survey 1976-77 (Owerri: Ministry of finance and economic development, Imo State, 1977)
This survey examines the agricultural life of a peasant farmers in Imo state of Nigeria. The aim is to collect quantitative information on agricultural structure, produce and challenges faced by the farmers and to proffer solution to enhance economic benefits of agricultural farming.
asm; 12/04/19
Loans
Keywords: Agriculture; Agricultural surveys; Agricultural surveys; Agriculture; Nigeria, Western Region